Merit and monetisation: A study of video game user-generated content policies - Amy Thomas (Internet Policy Review, 2023)
This article explores the alternative system of contractual regulation that permits monetised user-generated content (UGC) in the video game industry. By situating the user in an industry where it is possible to earn millions from "playing games", this article challenges the assumption in copyright doctrine that the user is a non-professional amateur, whose motivation for creating UGC is altruistic. The fundamental question in this article is about copyright incentives: who should reap the rewards for the creation of UGC? To answer this, the article examines the UGC policies of 30 popular game titles, revealing the distinct, but nuanced, concept of monetisation. The article illustrates how monetisation is constructed as a limited, merit-based allowance that both encourages and constrains the possibility of a user-led industry.
Keywords: 300; Copyright; User-generated content; Video games; Streaming; Monetisation